EFFECTS OF PREMENSTRUAL SYNDROME (PMS) ON PSYCHOLOGICAL DISTRESS WITH SOCIAL SUPPORT: A MODERATION MODEL - Noor Zainab; Hira Fatima; Mishal Zoha; Noor Fatima Aziz (International Journal of Contemporary Issues in Social Sciences, 2024)
The current study investigates the relationship between premenstrual syndrome and psychological distress with the moderating role of social support. The main objective of the current study was to examine how premenstrual syndrome increase the psychological distress and social support decrease the psychological distress. The data were collected from a sample of N=300 females was included in the study. The purposive sampling was used for collection of sample. The scales used to measure the variables are, The Premenstrual Symptoms Screening Tool (Steiner et al., 2003), Berlin Social Support Scale (Schwarzer & Schulz, 2000) and Depression Anxiety Stress Scale-21(Lovibond et al., 1995). Findings of Pearson correlation shows that premenstrual syndrome had a weak, negative and non-significant relation with social support, significantly positive moderate relation with psychological distress. Social support had a significant, negative and weak relation with psychological distress. Furthermore, findings of regression indicate that premenstrual syndrome is significantly positively predicts the psychological distress explained by 32% variance in psychological distress. Present study also reveals that there was no age difference in premenstrual syndrome. Furthermore, the moderation analysis found that social support had a significant moderation effect on premenstrual syndrome and psychological distress. This shows that the relationship between premenstrual syndrome and psychological distress is fully moderated by social support. So, overall all the findings of research are consistent with previous literature.